Yahoo Answers is shutting down on May 4th, 2021 (Eastern Time) and beginning April 20th, 2021 (Eastern Time) the Yahoo Answers website will be in read-only mode. There will be no changes to other Yahoo properties or services, or your Yahoo account. You can find more information about the Yahoo Answers shutdown and how to download your data on this help page.
Trending News
Write an equation of the circle whose DIAMETER is (5,4) and (-3,2).?
Please show work thank you so much
6 Answers
- SidLv 68 years agoFavorite Answer
Diameter distance will be given by
d = √ [ (5 - (-3))² + (4 - 2)²]
d = √68
=> radius ( r ) = √68/2 = √17
Now centre of the circle is the mid-point of the given extremes of the diameter and is given by
Center (h,k) = (5 - 3)/2, (4 + 2)/2 = (1.3)
Equation of the circle with centre (1,3) and radius √17 is,
(x - 1)² + (y - 3)² = √17²
x² + 1 - 2x + y² + 9 - 6y = 17
x² + y² - 2x - 6y - 7 = 0
- BattleaxeLv 78 years ago
Use the distance formula to find the diameter:
d = SQR[(x2 - x1)^2 + (y2 - y1)^2] = SQR[(-3 - 5)^2 + (2 - 4)^2]
= SQR(64 + 4) = SQR(68) = 2SQR(17) ~ 8.246
Radius = d/2 = 4.123
Use the midpoint formula to find the center of the circle:
[(x1 + x2)/2 , (y1 + y2)/2] =
[(5 + (-3))/2, (4 + 2)/2] = (1, 3)
A circle with radius = r and center (h, k):
(x - h)^2 - (y - k)^2 = r^2
(x - 1)^2 - (y - 3)^2 = 17
- .--
- ComoLv 78 years ago
C (1 , 3)
d² = 8² + 2² = 68
d = √68
r = √68 / 2
r² = 68/4 = 17
(x - 1)² + (y - 3)² = 17
- Wile E.Lv 78 years ago
x1 = 5
y1 = 4
x2 = - 3
y2 = 2
Center = C (x, y):
C [(x1 + x2) / 2, (y1 + y2) / 2]
C [(5 - 3) / 2, (4 + 2) / 2]
C (2/2, 6/2)
C (1, 3)
h = 1
k = 3
Diameter = d:
d² = (x2 - x1)² + (y2 - y1)²:
d² = (- 3 - 5)² + (2 - 4)²
d² = (- 8)² + (- 2)²
d² = 64 + 4
d² = 68
d = √68
d = 8.246
Radius = r:
r = 1/2 d:
r = 1/2 (8.246)
r = 4.123
Equation:
(x - h)² + (y - k)² = r²:
(x - 1)² + (y - 3)² = (4.123)²
(x - 1)² + (y - 3)² = 17
¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯
Source(s): 6/3/13 - How do you think about the answers? You can sign in to vote the answer.
- Anonymous8 years ago
The centre is ( (5-3)/2, (4+2)/2 ) = (1, 3)
and the diameter is sqrt( (-3-5)² + (2-4)²) = sqrt(64 + 4) = sqrt(68)
so the radius is ½sqrt(68) = sqrt(17)
Can you do it now?
- Anonymous8 years ago
Step 1: Prove the Riemann Hypothesis.
Thus, the problem trivializes from this step.